Analysis of the antiproliferative effects of 3-deazaneoplanocin A in combination with standard anticancer agents in rhabdoid tumor cell lines. Issue 3 (March 2015) - Unland, Rebekka; Borchardt, Christiane; Clemens, Dagmar; Kool, Marcel; Dirksen, Uta; Frühwald, Michael C.
Abstract : Rhabdoid tumors (RTs) are highly aggressive pediatric malignancies with a rather poor prognosis. New therapeutic approaches and optimization of already established treatment protocols are urgently needed. The histone methyltransferase enhancer of zeste homolog 2 (EZH2) is highly overexpressed in RTs and associated strongly with epigenetic silencing in cancer. EZH2 is involved in aggressive cell growth and stem cell maintenance. Thus, EZH2 is an attractive therapeutic target in RTs. The aim of the study presented here was to analyze the effects of a pharmacological inhibition of EZH2 alone and in combination with other anticancer drugs on RTs cells in vitro . The antitumor activity of the S -adenosyl-homocysteine-hydrolase inhibitor 3-deazaneplanocin A (DZNep) alone and in combination with conventional cytostatic drugs (doxorubicin, etoposide) or epigenetic active compounds [5-Aza-CdR, suberoylanilide hydroxamic acid (SAHA)] was assessed by MTT cell proliferation assays on three RT cell lines (A204, BT16, G401). Combinatorial treatment with DZNep synergistically and significantly enhanced the antiproliferative activity of etoposide, 5-Aza-CdR, and SAHA. In functional analyses, pretreatment with DZNep significantly increased the effects of 5-Aza-CdR and SAHA on apoptosis, cell cycle progression, and clonogenicity. Microarray analyses following sequential treatment with DZNep and 5-Aza-CdR or SAHA showed changes in global gene expression affecting apoptosis, neuronal development, and metabolic processes. In-vitro analyses presented here show that pharmacological inhibition of EZH2 synergistically affects the antitumor activity of the epigenetic active compounds 5-Aza-CdR and SAHA. Sequential treatment with these drugs combined with DZNep may represent a new therapeutic approach in RTs. Abstract : Supplemental Digital Content is available in the text.